ANALISIS UJI BEDA DIGITAL MARKETING, BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION (DALAM NEGERI VS LUAR NEGERI) DI MASA PANDEMI - Yunia Azis; Mia Mustika Destiani (MANAJEMEN DEWANTARA, 2022)
The high rate of layoffs during the pandemic caused purchasing power to drop drastically so that people prioritized buying primary needs over secondary needs such as fashion. This condition forces fashion entrepreneurs to switch to marketing their products using digital media so that existing brand awareness remains attached to consumers' memories. Fashion products originating from within the country have always competed with foreign products, so it is necessary to research whether there is a difference in consumer purchasing decisions for domestic and foreign products during the pandemic. The study was conducted to compare purchasing decisions during the pandemic, especially domestic and foreign fashion products through digital marketing and brand awareness. The research method used is descriptive and different test, using 2 fashion products as a comparison. The population of this study are women aged 20-40 years and often make transactions through online shops. Respondents were 30 people, the research instrument was a questionnaire. Validity and reliability were used to test the feasibility of the questionnaire, homogeneity and normality tests were used to test the sample, while the Independent sample t-test was used to compare the difference in the mean of the two different samples. This study obtained the results that in terms of digital marketing, brand awareness, and the decision to purchase foreign products were better developed than domestic products.